Improvement Of The Technology For Producing High-Quality Castings Through Out-Of-Furnace Treatment Of Molten Metal (American Economist: Journal of Economics Finance and Global Policy, 2026)
The present study is devoted to improving the technology for producing high-quality castings from carbon structural steels through the out-offurnace modification of molten metal. Experimental investigations were carried out under laboratory conditions using an IST-0.001 induction furnace. During the melting process, the molten metal was treated with different types of nickel-based modifiers, particularly ПН-ХН80С3Р3 (ПГ-СР3). The modifier was introduced into the melt in various proportions relative to the weight of the molten metal in order to influence the crystallization process and refine the microstructure of the casting. The chemical composition of the obtained samples was analyzed using SPECTROLAB-10M spectrometric equipment. Microstructural studies were performed at different magnifications to evaluate the phase composition and structural features of the cast steel. The results showed that the modification of molten metal increased the number of crystallization nuclei, leading to grain refinement and the formation of a more uniform structure.
Keywords: out-of-furnace treatment; molten metal modification; casting technology